Low high-density lipoprotein cholesterol levels predicting poor outcomes in patients with hepatitis B virus-related acute-on-chronic liver failure - Zhang, Yue; Chen, Peng; Zhang, Yun; Nie, Yuan; Zhu, Xuan (Frontiers in Medicine, 2022)
Background: Lipid profile disorders frequently occur in patients with advanced liver diseases. High-density lipoprotein cholesterol (HDL-C) levels decrease rapidly during acute conditions of some diseases, and HDL-C levels may be related to mortality in patients with HBV-ACLF. Materials and methods: A retrospective cohort study was conducted on 200 subjects with HBV-ACLF. The patients were separated into non-survivors and survivors according to their 28-day outcome. Univariate and multivariate Cox regression analyses were performed to identify predictors of mortality, and the performance of these predictors was evaluated by receiver operating characteristic (ROC) curve analysis. Kaplan–Meier analysis was performed to draw survival curves of HDL-C. Results: The 28-day mortality in the cohort was 27.0%. HDL-C levels differed markedly between non-survivors and survivors. In the multivariate analysis, HDL-C, the CTP, MELD and COSSHACLFII scores were identified as independent predictors for mortality (HR=0.806, 95% CI: 0.724-0.898; HR=1.424, 95% CI: 1.143-1.775; HR=1.006, 95% CI: 1.002-1.007; and HR=1.609, 95% CI: 1.005-2.575, respectively). Patients with lower HDL-C levels had a worse prognosis than those with higher HDL-C levels. In ROC analysis, the prognostic accuracy for mortality was similar between HDL-C (AUROC: 0.733) and the CTP, MELD and COSSHACLF II scores (AUROC: 0.753; 0.674 and 0.770, respectively). Conclusion: The HDL-C level may serve as a potential indicator for the prognosis of HBV-ACLF and can be used as a simple marker for risk assessment and selection of therapeutic options.